If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5+4x=7x-29
We move all terms to the left:
-5+4x-(7x-29)=0
We get rid of parentheses
4x-7x+29-5=0
We add all the numbers together, and all the variables
-3x+24=0
We move all terms containing x to the left, all other terms to the right
-3x=-24
x=-24/-3
x=+8
| -8x-10=-4 | | (18x+14)=(22x-20 | | 20x-30-8=10x+8-6x | | 8(y—1)-3y=6(2y-6) | | S=40000+500c | | 9(b+9)=36 | | 2/3d+5=-1/3 | | 2x-6=5+x | | 6c^2+7c-49=0 | | 7v-14=0 | | (x4+5x2-36)(2x2+9x-5)=0 | | -x-8=2x+28 | | (20x+5)=24x-1 | | 42-3u=4u | | 18-15=-2r/5+7r/15 | | 1/6x+3=8 | | 3=-2-k | | 3w+8–w=4w-2(w-4) | | 13/8=52/n | | -4(2x+5)=2x+30 | | .4x+x=6000000 | | 2/3(x+27=(3x-25) | | -1=-8+x/14 | | -3(1+4.5r)=-16.5 | | -15=-2(2x-1) | | 35p=910 | | (6x7)+(6x3)=x(7+3) | | 5(x+2)-x=2x-20 | | 2x-20+90=180 | | q^2+8q+16=-2q^2+9q+436 | | 5y-6=10y+54 | | 1/6x+3=7/9x-2 |